BUILDING BRIDGES THROUGH PLAY: AN INVESTIGATION INTO MONOPOLY GO! AS CATALYST FOR YOUTH SOCIAL INTERACTION - Jaya, Joana; Low, A. N.; Vasudevan, Asokan; Hasyim, Haryati (International Journal of Application on Economics and Business, 2024)
This study investigates how young people's social life are impacted by Monopoly Go! in the context of digital gaming. With the goal of analysing the game's communication elements, engagement reasons, and social repercussions, it fills knowledge gaps about the societal ramifications of digital games on social interaction. The literature study examines the evolution of Monopoly Go! from a classic board game to a mobile app, emphasising the game's ability to foster social connections even when players are separated by great distances. Through qualitative techniques including content analysis and in-depth interviews, the study looks into how the game affects young people's social connections. The game's ability to start talks, bring friends back together after the pandemic, and encourage peer influence and teamwork motivations is demonstrated by the findings. On the other hand, disputes that occur during in-game exchanges and the impact of in-game item commercialization on fair play are causes for concern. Future study should diversify its participant pool, ethical norms for community behaviour should be put in place, and the effects of commercialization on social dynamics inside gaming communities should be investigated. These revelations provide light on the intricate social dynamics, interpersonal relationships, and moral dilemmas present in online gaming environments.